The Qur’anic Authority in Strengthening Sufism Teaching at Majlis Pengkajian Tauhid Tassauf Indonesia (MPTTI) in Indonesia - Marhaban, Nawawi; Mawardi, Mawardi (Islamic Religious Education Departement, 2023)
The article overviewed the Qur’anic textual authority in practices and the concept of living in Qur’anic behaviours for Monotheism and Sufism, a council of study in Aceh province. As it is known for a board of study existence, Majelis Pengkajian Tauhid Tasawuf Indonesia (MPTTI) is growing more controversial regarding religious harmony in Islamic group society and its particular Sufism teaching. Nevertheless, despite these controversial phenomena, the council retains its teaching principles. The board exclusively refers to its teaching on Qur’an scriptures and verses as countermeasures of marginality and oppression. The committee believed in the authority of Sufism teaching, which was baselined on the Qur’an. The article projected how the council employs the scripture to formulate Sufism with a phenomenology approach to the engagement of living hadith in practice. Later, the board exploits the scripture as the source to establish critique for disavowing acceptance behaviours in society. The council intends to restore the communal into the proper stream of Islamic tradition. Parallel to these intriguing findings, the commission proclaims the Al Qur’an as an appropriate establishment of primary character reference. Eventually, the fascinating texts employed by the council also drive to strengthen the validity of council identity on national and even international coverage, which overlaps other boards in the region.